2008
DOI: 10.1002/uog.5349
|View full text |Cite
|
Sign up to set email alerts
|

Association of isolated short femur in the mid‐trimester fetus with perinatal outcome

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
105
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(124 citation statements)
references
References 24 publications
12
105
3
4
Order By: Relevance
“…A short FL is variably defined as <5th-10th percentile for gestational age [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16]. It is associated with congenital anomalies [2,3], aneuploidy (mostly trisomy 21) [2,3,6,7,8], skeletal dysplasia [4,5 ]and adverse pregnancy outcome [2,3,9,10,11,12]. Specifically, in the absence of anatomical or chromosomal malformations, isolated short FL has been associated with intrauterine growth restriction (IUGR), being small for gestational age (SGA) [2,3,9,10,11,12,13,14,15]and preeclampsia [11,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A short FL is variably defined as <5th-10th percentile for gestational age [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16]. It is associated with congenital anomalies [2,3], aneuploidy (mostly trisomy 21) [2,3,6,7,8], skeletal dysplasia [4,5 ]and adverse pregnancy outcome [2,3,9,10,11,12]. Specifically, in the absence of anatomical or chromosomal malformations, isolated short FL has been associated with intrauterine growth restriction (IUGR), being small for gestational age (SGA) [2,3,9,10,11,12,13,14,15]and preeclampsia [11,16].…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with congenital anomalies [2,3], aneuploidy (mostly trisomy 21) [2,3,6,7,8], skeletal dysplasia [4,5 ]and adverse pregnancy outcome [2,3,9,10,11,12]. Specifically, in the absence of anatomical or chromosomal malformations, isolated short FL has been associated with intrauterine growth restriction (IUGR), being small for gestational age (SGA) [2,3,9,10,11,12,13,14,15]and preeclampsia [11,16]. Short FL may also be explained constitutionally by ethnic origin and due to inaccurate dating [17,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Studies have confirmed that fetuses of asian mothers have shorter femurs and those of black mothers have longer femurs compared with fetuses of white mothers. 14 However, these ethnic differences were not confirmed by the study of Weisz et al 8 , and it is possible that other factors, such as maternal and paternal height, are more important than ethnicity alone in influencing fetal femur length. 15,16 In summary, isolated short femur, when present as lone soft marker, does not increase the background risk of fetal aneuploidy.…”
Section: Resultsmentioning
confidence: 91%
“…6,7 Early-onset intrauterine growth retardation was defined when EFW or AC < 5 th centile at the mid-trimester ultrasound scan. 8 Finding an isolated short femur at the time of midtrimester scan poses a challenge to the clinician: is there any fetal aneuploidy or is it a part of skeletal dysplasia or is it a normal variation? 9 There are studies which have shown that short femur is associated with increased risk of subsequent intrauterine growth retardation in pregnancy and small for gestational age neonates.…”
Section: Introductionmentioning
confidence: 99%